Comparison of Two Metabolic Simulators Used for Gas Exchange Verification in Cardiopulmonary Exercise Test Carts - Souren, Tjeu; Rose, Edward; Groepenhoff, Herman (Frontiers in Physiology, 2021)
Introduction: Metabolic simulators (MS) produce simulated human breaths for the purpose of verification of cardiopulmonary exercise test (CPET) equipment. MS should produce consistent identical breaths with known CO2 and O2 gas concentrations with variable breath rates and tidal volumes. Accuracy of a CPET metabolic cart depends on ongoing calibration and maintenance of the device, including intermittent verification with a MS. We compared two MS devices against two standard CPET systems. Methods: The Vacumed 17056 (Vacumetrics, Ventura, CA) and Relitech (Relitech Systems BV, Nijkerk, The Netherlands) were used with two standard metabolic carts (Vyntus CPX and Vyntus ONE, both Vyaire Medical, Mettawa, IL, USA). Tidal volume (VT) was set at two and three liters and breathing frequency ranged from 20 to 80 breaths per minute for each MS. At each set point, we measured three sets of 40 breaths. Primary outcome parameters collected were VT, oxygen consumption (V̇O2), carbon dioxide production (V̇CO2), and respiratory exchange ratio (RER). Results: VT, RER, V̇O2, and V̇CO2 results as obtained from both MS were all within the limits of acceptability, at both tidal volume settings, and all ventilatory rates. No significant trends were identified for either MS device. The tidal volumes from the MSs measured with both CPET carts were within the pre-defined acceptable ranges. The measurement results from the Relitech MS were closer to the expected values Conclusion: Verification of CPET equipment using either the VM or RT metabolic simulator, producing highly accurate and predictable simulated breaths of known composition, enable CPET laboratory managers to rely on the integrity of subject test data obtained during cardiopulmonary exercise testing.